2019
DOI: 10.1016/j.chb.2018.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Facebook, relatedness and exercise motivation in university students: A mixed methods investigation

Abstract: This is a repository copy of Facebook, relatedness and exercise motivation in university students: A mixed methods investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In recent years, there has been an increase in the number of studies using Facebook to deliver physical activity interventions in different populations [13][14][15]19,21,44]. As is the case in this study, Facebook has often been chosen based on its popularity [21] and the opportunity it offers to provide information and social support to the user [13].…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increase in the number of studies using Facebook to deliver physical activity interventions in different populations [13][14][15]19,21,44]. As is the case in this study, Facebook has often been chosen based on its popularity [21] and the opportunity it offers to provide information and social support to the user [13].…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Such engagement and support from others may lead to an increase in motivation and reinforcement to participate in physical activity [20]. The strategic use of social media to engage adolescents could result in stronger bonds that lead to increased feelings of relatedness and increased engagement in physical activity [21], and may provide a source of motivation to participate in physical activity [13,22]. Existing physical activity studies in adolescents and young people have found that frequently engaging with social media is associated with increased physical activity [14,19], although the challenge is identifying the strategies to engage adolescents, particularly as some research suggests that social media engagement is often passive [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we did not focus on the motivations for individuals' use of Facebook apps. Based on other behavioral technology research, we surmise that such motivations are likely mixed and lean toward hedonic motivation and other kinds of intrinsic motivation (e.g., relax, learn, discover) ( Posey et al., 2010 ; Lowry et al., 2015 ; Shibchurn and Yan, 2015 ; Church et al., 2017 ; Mekler et al., 2017 ; Divine et al., 2019 ). For example, individuals may use Facebook apps to relax and unwind (e.g., playing Facebook games) as opposed to being productive, which may alter information privacy attitudes and expectations.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In other words, qualitative research design in information technology research can offer important insights into the development, adoption, and usage of technology. Exclusive research on SNS and qualitative research designs have proved very effective in identifying and examining similar relationships (Ding, 2019;Divine et al, 2019).…”
Section: Methodsmentioning
confidence: 99%